2007
DOI: 10.1002/gps.1857
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 supplementation in mild to moderate Alzheimer's disease: effects on neuropsychiatric symptoms

Abstract: Supplementation with omega3 in patients with mild to moderate AD did not result in marked effects on neuropsychiatric symptoms except for possible positive effects on depressive symptoms (assessed by MADRS) in non-APOEomega4 carriers and agitation symptoms (assessed by NPI) in APOEomega4 carriers. ClinicalTrials.gov identifier: NCT00211159

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 48 publications
(48 reference statements)
7
108
1
2
Order By: Relevance
“…A total of 174 patients concluded the OmegAD study. Plasma fatty acid profi les and cognition and behavioral data have been published ( 7,26,27 ). Based on pretrial power calculation concerning cytokine profi les with a statistical signifi cance level of P < 0.05 and 80% power, a minimum of 20 patients was required to detect a difference of 30% between the 3 FAs and placebo groups through use of cytokine assays.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 174 patients concluded the OmegAD study. Plasma fatty acid profi les and cognition and behavioral data have been published ( 7,26,27 ). Based on pretrial power calculation concerning cytokine profi les with a statistical signifi cance level of P < 0.05 and 80% power, a minimum of 20 patients was required to detect a difference of 30% between the 3 FAs and placebo groups through use of cytokine assays.…”
Section: Methodsmentioning
confidence: 99%
“…Lopez et al [147], in their dietary intervention study, reported that fish intake was associated with lower odds of developing AD, but this did not reach statistical significance. Indeed, numerous x-3 supplementation studies [148][149][150][151] in AD patients have reported no significant improvement in AD measures. These investigators reported that supplementation with DHA (1.72 g)þEPA (600 mg) per day for six months did not show any improvement in cognitive deterioration in AD patients.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Gastrointestinal side effects resulted in several drop-outs (Freund-Levi et al, 2008;Kotani et al, 2006); and 3) AD patients have been dosed with 600 mg of lipoic acid daily for 48 month with no toxicity (Maczurek et al, 2008). Lipoic acid (600 mg) also is an approved therapy for treating diabetic neuropathy, in Germany.…”
Section: Ppi-1011: Safetymentioning
confidence: 99%